AN ANALYSIS ON LANGUAGE FUNCTION IN UTTERANCES PRODUCED BY CARL TO RUSSELL IN MOVIE “UP” - YUNITA, NANDA (Jurnal Ilmiah Mahasiswa FIB, 2013)
In daily life, people interact with each other by using language. Throughlanguage, people share information, ideas, or feelings with one another. This study isintended to analyze the language function that can be found in a movie entitled Up.There are two problems found in the utterances produced by Carl to Russell. It attemptsto answer two problems, which are: (1) what kinds of language functions used by CarlFredricksen in the dialogues of the movie Up(2) how the language functions help thewriter in constructing the message in the movie Up.  The writer applied qualitative approach in this study since all data are in theform of words. The type of the research is content analysis since it intended to analyzethe content of the data, which are in the form of movie script to find the languagefunctions. In analyzing the data, the writer used the theory of Halliday (1992).  Based on the result of the analysis and language function of Halliday, it is foundthat there are seven languagefunctions according to Halliday (1992) in the utterancesproduced by Carl to Russell in movie Up. They are instrumental, regulatory,representational, interactional, personal, heuristic and imaginative functions. The mostfrequently used regulatory function which intended to manage the behavior of others, tomanipulate the person in the environment, which is known as do as tell you function.Each utterance carries its own message based on the language functions it has.Therefore, it is important to know the topic being discuses and the context where thedialogue occurs.  Based on the research question and discussion of the data presentation andanalysis, the conclusion can describe dealing with the language function in Up themovie that is used by Carl as the elderly man and Russell the young boy who stuck inadventure with Carl. The writer suggest for the further researcher that since this study isconducting language function by Michael Halliday, it will be more interesting toanalyze by using another theory on language function. Keywords: Language Function, Message, Movie Dialogue